GENDER DIFFERENCES IN BULLYING AND VICTIMIZATION AMONG EARLY ADOLESCENTS IN JORDAN - Kareem M. Jaradat, Abdul (PEOPLE: International Journal of Social Sciences, 2017)
This study investigated gender differences in bullying and victimization among Jordanian early adolescents. The sample consisted of 330 students (162 males, 168 females) in the seventh and eighth grades. These students were randomly selected from six public schools. Two scales were used, one for bullying and the other for victimization, each of which composed of ten items. Results of independent samples t-tests indicated that males had significantly higher scores than females on each of the two scales. Furthermore, chi-square tests showed that males were more involved in bullying than females across bullying groups. There were also significant differences in terms of the locations of bullying. For boys, bullying most often occurs on the way home from school; while for girls, bullying often occurs in the classrooms. It was found that "hitting or pushing other students" is the most common form of bullying used by adolescent male bullies, and that "calling other students with bad names" is the most common form of bullying used by adolescent female bullies.